Influence of preparedness on caregiver burden, depression, and quality of life in caregivers of people with disabilities - Uhm, Kyeong Eun; Jung, Heeyoune; Woo, Min Woo; Kwon, Hyo Eun; Oh-Park, Mooyeon; Lee, Bo Ram; Kim, Eun Joo; Kim, Jung Hwan; Lee, Seung Ah; Lee, Jongmin (Frontiers in Public Health, 2023)
Introduction Caregiver preparedness is defined as the perceived preparation of caregivers to care for the physical and emotional needs of the patient. Purpose This study investigated caregiver preparedness and its influences on caregiver burden, depression, and quality of life (QoL) in caregivers of individuals with disabilities. Methods We conducted a multicenter cross-sectional survey study on caregivers caring for patients with disabilities. Sociodemographic characteristics were collected via questionnaires. The Preparedness for Caregiving Scale (PCS), Burden Interview (BI), Center for Epidemiologic Studies Depression Scale (CES-D), and EuroQol-Visual Analogue Scale (EQ-VAS) were administered. Results A total of 151 caregivers were enrolled. The mean age of caregivers was 53.7 ± 12.4 years, and 80.8% were female. The majority of participants were the main caregivers of patients with stroke, spinal cord injury, or traumatic brain injury. The mean PCS score was 2.1 ± 0.9, demonstrating significant relationships with BI (r = −0.512, p < 0.001), CES-D (r = −0.622, p < 0.001), and EQ-VAS (r = 0.441, p < 0.001). The CES-D was significantly associated with the PCS after controlling other variables. However, PCS did not show any correlation with the duration of caregiving or amount of time spent per day on caregiving. Discussion The clinical implications of this study are that higher caregiver preparedness is a predictor of less caregiver burden and depression, and better QoL. However, preparedness did not increase as the duration or time spent on caregiving was extended. Therefore, efforts to enhance the caregivers’ preparedness are required to reduce caregiver burden and improve health outcomes for both caregivers and patients.